2017
DOI: 10.1080/21693277.2017.1401495
|View full text |Cite
|
Sign up to set email alerts
|

A methodology for near net shape process feasibility assessment

Abstract: department of design, Manufacturing and engineering Management (dMeM), university of strathclyde, glasgow, uK ABSTRACT Manufacturing engineers are frequently asked to select the best process for creating components but often the judgement is qualitative rather than quantitative. This paper presents a methodology (DCFA -Differential Cost and Feasibility Analysis) for assessing the technological and economic feasibility of using Near Net Shape (NNS) processes for the manufacturing of specific components. The met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…A frequently used noise reduction method is the installation of a noise reduction valve cage with holes drilled in the cage, which can only satisfy the linear flow characteristics due to the uniform distribution of the holes [21,22]. Sotoodeh [23] investigated valve cages with many small holes drilled in the control valve to divide the flow into many small flows, using this design to reduce noise.…”
Section: Introductionmentioning
confidence: 99%
“…A frequently used noise reduction method is the installation of a noise reduction valve cage with holes drilled in the cage, which can only satisfy the linear flow characteristics due to the uniform distribution of the holes [21,22]. Sotoodeh [23] investigated valve cages with many small holes drilled in the control valve to divide the flow into many small flows, using this design to reduce noise.…”
Section: Introductionmentioning
confidence: 99%
“…As a direct result of this analysis, centrifugal casting was adopted for valve cage production generating 26.5%, saving 490 machining hours and 18.9 tons of raw material. The NNS process feasibility study and application details can be found in [46].…”
Section: Resultsmentioning
confidence: 99%
“…Some efforts on NNS document both reduction of waste in specific manufacturing processes and achievement of specific properties with low defect rates. This is borne out by few existing papers [ 17 , 19 , 20 ] that report aiming for a near net shape while also focusing on attendant functionality, mechanical properties and microstructure without explicit reference to surface integrity . Surface integrity considerations are significant because of their potential to enhance product life [ 21 , 22 ], which is vital to sustainable development .…”
Section: Frugal Manufacturingmentioning
confidence: 99%
“… existing NNS process tolerances surface integrity properties process cost no. processes wastage 1 centrifugal casting and machining [ 20 ] yes no yes unknown 3 0 2 roll forming [ 32 ] yes no yes low 1 0 3 isothermal forging [ 29 ] yes no yes unknown 1 minimal 4 flow forming [ 23 ] yes no yes high 1 0 5 cold forging of spur gear [ 19 ] yes no yes unknown 2 minimal 6 cold forging of tulip shaft [ 19 ] yes no yes unknown 3 minimal 7 ...…”
Section: Gauging Frugality Of Processesmentioning
confidence: 99%